THE INFLUENCE OF INTAKE VALVE CLOSE TIMING ON THE ENVIRONMENTAL PERFORMANCE OF A SPARK IGNITION ENGINE USING GASOLINE AND NATURAL GAS - Tadas VIPARTAS; Alfredas RIMKUS; Jonas MATIJOŠIUS (Transport Problems)
The tightening of environmental requirements has forced car manufacturers to look for various ways to reduce exhaust gas emissions. The existing structural solutions of internal combustion engines allow this type of pollution to be reduced by adjusting the intake valve timing. This is especially relevant when it comes to reducing spark ignition engine emissions when using natural gas as fuel. In this study, a wide range of intake valve timing adjustments from 24° to 54° every six crank angle degrees was taken at a constant engine speed (n = 2500 rpm) and different loads and fixed excess air ratios (λ = 1). The changes in oxygen (O2), carbon monoxide (CO), carbon dioxide (CO2), nitrous oxide (NOx), methane (CH4), and propane (C3H8) gas emissions were observed in the aforementioned intake valve timing range.